Ovarian Stem Cells—the Pros and Cons - Evron, Ayelet (Libertas Academica, 2013)
The potential for postnatal de novo oogenesis in mammals and in humans has become very controversial in the fields of reproductive science and biology. Historically, it has been thought that females of most mammalian species lose the ability to produce oocytes at birth. A contemporary understanding of stem cell biology together with novel experimental methods has challenged the model of a prenatal fixed ovarian primordial follicle pool that declines with age. Researchers have suggested replenishment of post-natal oocytes by germ-line stem cells (GSCs). According to this theory, GSCs produce oocytes and primordial follicles throughout the lifetime of the adult female. This review describes recent approaches supporting the revolutionary idea of de novo oogenesis in mammals and humans of reproductive-age and provides counter arguments from opponents of this novel and innovative concept.